TUMPANG TINDIH PUTUSAN PENGUJIAN PERAT34 URAN PERUNDANG-UNDANGAN DI MAHKAMAH AGUNG DAN MAHKAMAH KONSTITUSI DITINJAU DARI ASAS KEPASTIAN HUKUM - Michael Michael; Rasji Rasji (Jurnal Hukum Adigama, 2021)
The author made this thesis with the title "Overlapping Decisions on Testing Legislation in the Supreme Court and the Constitutional Court Judging from the Principle of Legal Certainty" because as a state of law and the regulation of guaranteeing constitutional rights (Article 28 D paragraph 1 of the 1945 Constitution of the Republic of Indonesia) which in this case This is a legal certainty that is often violated by the enactment of laws and regulations. Therefore, as an effort to guarantee that regulations do not conflict with each other, a mechanism for reviewing laws and regulations is arranged. The Supreme Court decided to review the legislation under the law against the constitution, but the problem was that this last resort actually resulted in legal uncertainty again occurring when the decisions of the Supreme Court and the Constitutional Court regarding the review of laws and regulations contradict one another. each other. Therefore, the writing of this thesis will focus on finding the source of the overlapping problem and possible solutions to solve these problems.